1996
DOI: 10.1038/380723a0
|View full text |Cite
|
Sign up to set email alerts
|

Sequential activation of ICE-like and CPP32-like proteases during Fas-mediated apoptosis

Abstract: Binding of Fas ligand or an agonistic anti-Fas antibody induces apoptosis in Fas-bearing cells. The interleukin-1Beta-converting enzyme (ICE) is a cysteine protease that is involved in apoptosis induced by various stimuli, including Fas-mediated apoptosis. Several ICE homologues have been identified, and these are subdivided into three groups (ICE-, CPP32-, and Ich-1-like proteases). We show here that specific inhibitors of ICE- or CPP32-like proteases can inhibit Fas-mediated apoptosis. Transient ICE-like act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
608
7
1

Year Published

1997
1997
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 933 publications
(648 citation statements)
references
References 29 publications
32
608
7
1
Order By: Relevance
“…Caspases have been suggested to constitute a protease cascade, based on observations that their active forms directly cleave the precursors of other family members in vitro to activate them (reviewed by Martin and Green, 1995). We and others have recently reported that a protease cascade involving caspase-1-like and caspase-3-like proteases operates to transduce apoptotic signals in vivo (Shimizu et al, 1996a;Enari et al, 1996).…”
Section: Introductionmentioning
confidence: 94%
“…Caspases have been suggested to constitute a protease cascade, based on observations that their active forms directly cleave the precursors of other family members in vitro to activate them (reviewed by Martin and Green, 1995). We and others have recently reported that a protease cascade involving caspase-1-like and caspase-3-like proteases operates to transduce apoptotic signals in vivo (Shimizu et al, 1996a;Enari et al, 1996).…”
Section: Introductionmentioning
confidence: 94%
“…It has also been reported that thymocytes from caspase-1-de®cient mice are resistant to Fas-mediated apoptosis, indicating the direct involvement of caspase-1 itself in this process of thymocyte death (Kuida et al, 1995). Sequential activation of caspase-1(-like) and caspase-3(-like) proteases has been shown to occur in Fas-mediated apoptosis of mouse lymphoma cell line (Enari et al, 1996). Recently, a novel caspase family protease, caspase-8 (MACH/FLICE/Mch5),with two FADD-like domains has been described to be involved in transduction of death signals from Fas and TNF receptor directly to other caspase family proteases (Boldin et al, 1996;Muzio et al, 1996;FernandesAlnemri et al, 1996).…”
Section: Introductionmentioning
confidence: 97%
“…Ten members of caspase family proteases have recently been identi®ed , and among them caspase-1 (ICE)(-like), caspase-3 (CPP32/Yama/apopain)(-like) and caspase-2 (ICH-1) proteases are implicated in apoptosis (reviewed in Martin and Green, 1995). The caspase family proteases have been suggested to constitute a protease cascade (reviewed in Martin and Green, 1995;Enari et al, 1996;Shimizu et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The death domain recruits FADD upon Fas activation (Kischkel et al, 1995), this then recruits and activates caspase 8 (Muzio et al, 1996;Boldin et al, 1996). Other caspases, including 1 and 3, are subsequently activated (Enari et al, 1996) and caspase activation is necessary for Fas-mediated apoptosis (Tewari and Dixit, 1995).…”
Section: Introductionmentioning
confidence: 99%